Digital marketing for ring craftsmen in Basen Village, Kotagede, Yogyakarta - Eko Muh Widodo; Meidar Hadi Avizenna; Tuessi Ari Purnomo (Community Empowerment, 2022)
One of the producers of handcrafted rings and jewelry is Mbasen, whose crafts are based on customer preferences. 9 workers can only produce 10–12 pairs of rings each day, which is still below the ideal manufacturing capacity. The marketing component has also not been utilized to its full potential. Community service projects are carried out to help the handmade ring jewelry business overcome the issues of low manufacturing capacity and ineffective marketing strategy. The approach used to provide the assistance is called community development, and it consists of four stages: socializing, training, technology deployment, and ongoing support. The technology that will be applied is information about Search Engine Optimization (SEO) which is used to expand the market through digital marketing and digital branding for website creation. To improve production capacity, the team additionally helped with the procurement of power inverters.